(untitled) (Bangladesh Journal of Bioethics, 2012)
Historically, ethics has been considered the province of religion i.e moral theology and large, still remains so. In most cases religion provides an important answer to the question, why one should act ethically. The ancient Greeks were the first to examine ethics philosophically and thus independently to religion . The major proponents of it were Socrates, Plato and Aristotle in the 5th & 4th centuries B.C. Now a days we can see lack of ethics everywhere of our life. This article try to find out –where & what are the ethics we are lacking behind in our day to days life and it`s probable remidies. Morality should be practiced and should start from the –“DINNING TABLE”. Beside this Government should pass down policies, which will facilitate this practice to get good citizens. The main thrust of modern ethics or moral philosophy is to attempt to lay the foundations of ethical conduct, which should be bear in mind with good faith. DOI: http://dx.doi.org/10.3329/bioethics.v1i3.9635 Bangladesh Journal of Bioethics 2010; 1(3): 52-57